Solvent Extraction of Zr and Hf from HCl by Aliquat 336 using a Flow-Type Extraction Apparatus Toward Online Chemical Studies of Element 104, Rutherfordium. Issue 3 (15th April 2020) - Kasamatsu, Yoshitaka; Kondo, Narumi; Nakamura, Kouhei; Kuboki, Yuki; Ninomiya, Hidemi; Shigekawa, Yudai; Watanabe, Eisuke; Yasuda, Yuki; Toyomura, Keigo; Nagase, Masahiro; Yokokita, Takuya; Komori, Yukiko; et al.
ABSTRACT: Chemical studies of transactinide elements (atomic number Z ≥ 104) are of great importance to understand the relativistic effects; however, the experimental methodology is limited owing to the single atom situation and short lifetimes of the heavy atoms. Herein, we report the successful establishment of a new solvent extraction method for transactinide elements using a flow-type solvent extraction apparatus. The developed apparatus has a reaction unit in which PTFE chips are packed to shorten the time required for the transfer of metal complexes between the aqueous and organic phases. Equilibrium distribution ratios were obtained for Zr and Hf: the homologues of element 104, rutherfordium (Rf), in a short time considering the half-life of 261 Rf as 68 s. In addition, the developed extraction apparatus was connected to an online transportation system for the nuclear reaction products at an accelerator, and online solvent extraction experiments were conducted with the short-lived nuclear reaction products of 89m, g Zr and 173 Hf. Distribution ratios consistent with the equilibrium ratios were successfully acquired. The solvent extraction system for experiments on Rf was thus established, and the optimal experimental conditions were determined.